Formação de leitor literário na escola pública : problemas e desafios de duas escolas de Campo Mourão - Uller, Luciene Aparecida Sgobero (2014)
The objective of this theoretical and practical research is a reflection about the difficulty of the Public School Institution, which are represented by two schools surveyed in Campo Mourão, to form effective literary readers, despite of the investments made in school over the last years by its provider SEED/ MEC, both in infrastructure (textbooks, tools, technology, etc.) and in continuing education for teachers and other education professionals. For the proposed analysis, a bibliographical research was done, which the theoretical base is constituted by knowledge related to reading, literature and literacy, as well as studying a case of ethnographic approach, involving a questionnaire, accomplished in the end of November 2012, in two sixth year classrooms of two schools in Campo Mourão, being one in downtown and the other in the city?s outskirts, labeled A and B respectively. The questions were organized, to investigate how the school uses its structural and technological resources available to work with reading to form literary readers. In this regard, the research started with questions about the library, the computer lab, internet and USB TV and finally, questions about pupil/reading relationship. The students answers, both "School A" and "B", raised a discussion about the results pointing to the proposition that, more than physical space, what makes the difference in reader formation process are the actions which the school can implement together with the students, in favor of this formation. This research also points to the importance of the work of school reading directed for multiple literacies, using technologies available in the school environment, by using methodologies that prioritize the differences.